Organizational Justice, Financial Compensation, Leadership, Job Satisfaction and Employee Performance - Parwati, Ni Luh Heka; Darma, Gede Sri (Universitas Pendidikan Ganesha, 2025)
The globalization era encourages Indonesia to improve the quality of human resources (HR) as the primary driver of national development. Udayana University, as a Public Service Agency, relies heavily on lecturers and educational staff; however, the increasing number of retired civil servants and reliance on contract employees have created challenges in maintaining performance. This study aims to evaluate the effect of organizational justice, financial compensation, and leadership on job satisfaction and employee performance. A quantitative survey was conducted with a saturated sample of 169 contract employees in the General Bureau of Udayana University. Data were analyzed using Partial Least Squares (PLS) with SmartPLS 4.1.0. The results show that job satisfaction has a significant positive effect on employee performance, and leadership has a significant positive effect on job satisfaction. In contrast, organizational justice and financial compensation do not have a significant direct effect on either employee performance or job satisfaction. These findings highlight the importance of non-financial and cultural factors in enhancing employee outcomes and provide practical implications for university management to strengthen leadership practices, intrinsic motivation, and organizational culture.